2017
DOI: 10.1088/1361-6463/aa7157
|View full text |Cite
|
Sign up to set email alerts
|

Reduced electrical performance of Zn enriched ZnTe nanoinclusion semiconductors thin films for buffer layer in solar cells

Abstract: Closed space sublimation (CSS) technique was employed to deposit thin films of Zinc Telluride

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Waqar Mahmood 1,2,3 * , Junaid Ali 4 , Andrew Thomas 2,5 , Saif ullah Awan 6 , Mark Jackman 2 , Anwar-ul-Haq 7 , M. Umair Hassan 4 , Nazar Abbas Shah 3 Introduction II-VI semiconductor family has received a lot of attraction for their tunable optical and electrical properties [1][2][3][4]. Cadmium sulfide (CdS) is a member of II-VI chalcogenide semiconductor family.…”
Section: Role Of Ag 1+ Substitutional Defects On the Electronic And Omentioning
confidence: 99%
See 1 more Smart Citation
“…Waqar Mahmood 1,2,3 * , Junaid Ali 4 , Andrew Thomas 2,5 , Saif ullah Awan 6 , Mark Jackman 2 , Anwar-ul-Haq 7 , M. Umair Hassan 4 , Nazar Abbas Shah 3 Introduction II-VI semiconductor family has received a lot of attraction for their tunable optical and electrical properties [1][2][3][4]. Cadmium sulfide (CdS) is a member of II-VI chalcogenide semiconductor family.…”
Section: Role Of Ag 1+ Substitutional Defects On the Electronic And Omentioning
confidence: 99%
“…It is a potential candidate for extensively uses in the technology of optoelectronics, photovoltaic and photo catalysis devices because of its amazing electrical and optical properties (i.e. emission in visible range) [2][3][4]. Other great impending applications include its usage as photo detectors, optical filters, solar cells applications and photo-resistive switches [4][5][6].…”
Section: Role Of Ag 1+ Substitutional Defects On the Electronic And Omentioning
confidence: 99%
“…It can be observed that some large particles or droplets could be observed on the surface of the film, as shown by the white dots. [21] The atomic ratio of Zn and Te is about 54:46, indicating that Te vacancies appear in ZnTe films. [20] X-ray photoelectron spectroscopy (XPS) spectra of Zn 2p and Te 3d of ZnTe film are shown in Figure 2c,d, respectively, well consistent with the fingerprints of Zn and Te atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The rough surface thin films are synthesized using closed space sublimation technique for solar cell applications [75][76][77][78][79]. The complete device with highest reported efficiency of more than 16 % was fabricated using this technique along with chemical bath deposition.…”
mentioning
confidence: 99%
“…Pre-annealing process was started once the required source and substrate temperatures achieved with deposition time, the source lamp was switched off and the substrate lamp was still 'on' till the source temperature was dropped to substrate temperature. At the end of deposition, the source-substrate temperatures were switched 'off' and the chamber was left for cooling down to room temperature under vacuum to avoid oxidation [75][76][77][78][79][80][81].…”
mentioning
confidence: 99%